SIR SAYYID AHMAD KHAN DAN REKONSTRUKSISME PENDIDIKAN ISLAM ALA INDIA - Yecki Bus (Universitas Islam Negeri Imam Bonjol Padang, 2015)
ir Sayyid Ahmad Khan was an Indian Muslim leaders with a view of the famous modernist intellectualwho stamped as secularist because he tended to rationality and naturalism. Beside as a political activist whopioneered the birth of Pakistan, he was also a thinker as well as a modernist of Islamic education in India.One of his important ideas of Islamic education was to combine the concept of western-modern sciences andIslamic studies. This combination system of education is one of the tops in the Muslim world. Nowdays, thesystem is widely adopted by contemporary Islamic educational institutions with each version. The purposes ofthis pattern are not only to produce Muslim intellectuals are experts in the field of modern science and catch upwith the West, but also individuals who are resilient in Islam. This paper analyzes the results of his experimentsand sees the effect on the dynamics of Islamic education up to now. Among the things that were observed fromthis system is criticism in learning science studies are actually good, but it does not filter frame of a typicalWestern uphold the principle of secularism, positivism and materialism. It accused can make scientific Muslimintellectuals but materialist and westernist.